Synergic sensing of light and heat emitted by offshore oil and gas platforms in the South China Sea - Yujia Qiu; Xiao-Ming Li; Lin Yan; Zhongzhong Chen (International Journal of Digital Earth)
Facing the growing global demand for oil resources and the industry’s commitment to decarbonization, there is a need for customized monitoring of oil and gas (OG) platforms. Remote sensing has proved an effective approach for OG platform observation compared to in-situ surveys. However, coarse spatial resolution and unbefitting spectra confine the application in monitoring platform activities. The Sustainable Development Science Satellite 1 (SDGSAT-1) has a comprehensive advantage, providing high spatial resolution (up to 10 m) and wide swath (300 km) imaging capability while enabling synchronous observation of the Glimmer Imager (GLI) and Thermal Infrared Spectrometer (TIS) at night. In this study, we demonstrated for the first time the synergic application of the SDGSAT-1 GLI and TIS to observe offshore OG platforms, probing their peculiar activities of associated gas flaring. By incorporating GLI visible colour bands, we developed an algorithm for gas flaring detection, pinpointing 113 active OG platforms in the South China Sea. The SDGSAT-1 not only pinpoints the offshore OG platforms but also provides insights into understanding their light- and heat-emitting variations. These findings highlight the competence of SDGSAT-1 in tracking the operational status of OG platforms and contributing to further refining the OG platform inventory.